Fall in the Fire-Bomb Fighters!-poster 1940 (London)
1942 1939-1945 "Fall in the Fire-Bomb Fighters!-poster 1940" [HFR0017], c. 1940 Ministry of Home Security poster issued c.1940 with a quote by Herbert Morrison. Incendiary bombs were dropped in clusters to spread fires. In September 1940, a Fire Watchers Order was issued compelling men to fire watch for a maximum of 48 hours per month. Factories and large buildings were responsible for providing their own firewatchers.